2017
DOI: 10.18203/2319-2003.ijbcp20175072
|View full text |Cite
|
Sign up to set email alerts
|

Usnic acid biological activity: history, evaluation and usage

Abstract: Since Usnic acid (UA) was isolated from lichen metabolite in 1844, a lot of studies were conducted on it and now it became commercially available in the market. Its wide availability in different lichen species, being isolated easily, and high purity of the isolated product make it an excellent base for producing new pharmaceuticals. In this review the different usage of UA was summarized. It was utilized as an antioxidant, anti-proliferative, antimicrobial and antiprotozoal, larvicidal and insecticidal, antif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…The antibacterial activity of C. uncialis extracts has been proven for the first time in our previous studies, in which we demonstrated a high activity of the C. uncialis acetone extract (CUE) on methicillin-resistant Staphylococcus aureus (MRSA) strains (Studzińska-Sroka et al, 2015). These interesting findings, as well as previous information about antimicrobial activity of UA (Galanty et al, 2012;Alahmadi et al, 2017;Galanty et al, 2019), prompted us to expand the study on the activity of CUE against clinical pathogenic strains responsible for skin and wound infections, which demonstrate resistance to antibiotics. In our research we also compared the cytotoxic effect of the tested substances by employing in vitro studies with human keratinocyte cell cultures (HaCaT).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…The antibacterial activity of C. uncialis extracts has been proven for the first time in our previous studies, in which we demonstrated a high activity of the C. uncialis acetone extract (CUE) on methicillin-resistant Staphylococcus aureus (MRSA) strains (Studzińska-Sroka et al, 2015). These interesting findings, as well as previous information about antimicrobial activity of UA (Galanty et al, 2012;Alahmadi et al, 2017;Galanty et al, 2019), prompted us to expand the study on the activity of CUE against clinical pathogenic strains responsible for skin and wound infections, which demonstrate resistance to antibiotics. In our research we also compared the cytotoxic effect of the tested substances by employing in vitro studies with human keratinocyte cell cultures (HaCaT).…”
Section: Introductionsupporting
confidence: 83%
“…Most of studies on antibacterial activity of UA were focused on its (+) enantiomer, which usually demonstrated an increased activity in comparison to its (-) form (Galanty et al, 2012). In addition to antibacterial properties, UA has also antioxidant, antiproliferative, antiprotozoal, larvicidal and insecticidal, antifungal, antiviral, algicidal, anti-inflammatory, pain-relieving and antipyretic properties, as has been demonstrated by in vivo and in vitro studies (Alahmadi, 2017).…”
Section: Introductionmentioning
confidence: 90%
“…Lethality and cytological changes in brine shrimp larvae are easy to assess in these organisms [ 54 ], making screening very fast and efficient. A study on liver cells [ 55 ] showed an increase in lipid droplet content and fragmentation of the endoplasmic reticulum in conditions of exposure to usnic acid. We consider these cytological aspects similar to those observed in the organisms exposed in UBDE ( Figure 5 b–e).…”
Section: Discussionmentioning
confidence: 99%
“…The metabolomics of this species belongs to different classes of chemical compounds: depsides (barbatic acid, methyl-8-hydroxy-4- O -demethylbarbatate, baeomycesic acid, 8-hydroxybarbatic acid), depsidones (connorstictic acid, fumarprotocetraric acid, hypoconstictic acid, lobaric acid), lipids (polyhydroxylated lipids), and dibenzofurans (usnic acid, placodiolic acid) [ 21 ]. Of all these lichen secondary metabolites, usnic acid [ 22 ] is by far the best known [ 23 ] and responsible for most bio-activities [ 24 ] of the U. barbata and, at the same time, of all lichens of the Usnea genus [ 25 ].…”
Section: Introductionmentioning
confidence: 99%